Learning More About Active Learning. - Stemp-Morlock, Graeme (Communications of the ACM, 2009)
The article discusses improvements and innovation of the field of active learning algorithms that are creating large savings in label complexity. In an attempt to prevent junk email from reaching its intended recipients, early spam filters relied on a combination of brute force computing with passive learning and refined processing with active learning, the article indicates. Commentary is provided by Ph.D. candidate Steve Hanneke on improvements made to active learning processes and informative examples as well as activized learning.